Potential of barn swallow feces as a non-destructive biomonitoring tool for anthropogenic pollutants: Site and chemical specificities and an evaluation of soil contaminants. Issue 1 (1st January 2021) - Imaeda, Chihiro; Niizuma, Yasuaki; Ohura, Takeshi
ABSTRACT: In this study, we investigated the potential of swallow feces as a bioindicator to evaluate soil pollution from anthropogenic sources. This biomonitoring was performed with trace elements, polycyclic aromatic hydrocarbons (PAHs), and their chlorinated derivatives (ClPAHs) as pollutants. The concentration of total trace elements targeted was reasonably consistent in both soil and fecal samples. The composition of individual trace elements also showed a similar profile across the sampling sites. The concentration of total PAHs varied in both soil and fecal samples among the sites, whereas their composition showed a similar profile. There were no significant correlations between total PAH or total ClPAH concentrations in either soil or fecal samples. This suggests that the sources and metabolic pathways in swallows may differ between PAHs and ClPAHs. Predictions of individual contaminant levels in soil samples were made from corresponding datasets of the feces using partial least squares analysis, and showed significant correlations based on the magnitude order. It permitted to roughly complement the levels of contaminants in the soils by the estimated equation.